Depression and Anxiety Disorders in Patients With Inflammatory Bowel Disease - Hu, Shurong; Chen, Yiping; Chen, Yan; Wang, Caihua (Frontiers in Psychiatry, 2021)
Psychological health is a significant yet neglected aspect of inflammatory bowel disease (IBD) patient care, with challenges in identifying proper treatments and mental health resources. The most common psychological conditions in patients with IBD are anxiety and depression. The increased prevalence of these psychiatric disorders calls for a psychiatric screening of every person diagnosed with IBD at the time of initial consultation. There are simple, accessible, and clinically feasible tools available to screen for psychological problems. Psychological approaches may be as or even more important as a treatment modality. Herein we discuss the three main areas of IBD psychological comorbidities of depression and anxiety: 1) the prevalence and risk factors associated with anxiety and depression disorders with IBD patients; 2) diagnose of psychological disorders with IBD patients; 3) psychological treatment with IBD patients. The integrated approach of management of IBD patients, consisting of teams of gastroenterologists and psychiatrists, should be incorporated as a standard of care.